High-intensity cycling performed prior to resistance exercise does not influence mTORC1-signaling and the rate of muscle protein synthesis in the triceps brachii - Moberg, M.; Apró, W.; Ekblom, B.; Blomstrand, E. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: Endurance exercise can influence strength training adaptations when performed concurrently, with both inhibition (Kreamer 1995) and augmentation (Lundberg 2012) of muscular hypertrophy being reported. Our lab has set out to conduct a series of studies to examine the influence of endurance exercise on the acute stimulatory effect of resistance exercise on anabolic processes. In the present study, the effect of endurance exercise on a previously inactive muscle was investigated. The aim was to examine the influence of resistance exercise on mTORC1-signaling and rate of protein synthesis in the triceps brachii muscle with or without preceding intervals of high-intensity cycling. Methods: Eight trained males performed, in a randomized fashion, two sessions of heavy resistance exercise (RE) with the triceps muscles, where one session was preceded by intervals of high-intensity cycling (E+RE), 5 x 4 min at 85% of VO2 peak. Mixed muscle protein fractional synthetic rate (FSR) was measured at rest, prior to exercise, and during a 3 hour recovery period following exercise by continuous infusion of L-[ring-13C6] phenylalanine. Muscle biopsies from the triceps brachii was collected twice at rest reparated by three hours, directly after resistance exercise and following 90 and 180 min of recovery. Signalling in the mTORC1-and AMPKpathway was assessed using western blot technique. Results: The same amount of work with regard to load, total number of repetitions and total time under tension was performed in the two trials. Muscle protein FSR increased from 0.050 ± 0.006 %/h at rest to 0.078 ± 0.008 and 0.082 ± 0.0016 %/h following E+RE and RE, respectively, with no difference between trials. Phosphorylation (P) of AMPK T172 was increased by 45-65% directly after exercise, similarly in both conditions, and regressed to a level approx. 20% lower than baseline following 180 min of recovery. P-mTOR S2448 was increased 76 and 108% above rest directly after the E+RE and RE, respectively, and remained elevated in both trials during the entire recovery period. P-eEF2 T56 was 20-36% higher directly after exercise but fell to a level that was 30-36% lower than pre-exercise and remained reduced during the entire recovery, with no difference between trials. Conclusion: High-intensity endurance cycling does not influence the acute stimulation of anabolic signalling and muscle protein synthesis in the triceps brachii following resistance exercise.